Internalisasi Hukum Islam dan KUHP Baru dalam Penanggulangan Tindak Pidana Perzinaan - Ayunisa, Qurota; Rismana, Daud; Huda, Muhammad Nurul; Munjiyah, Amrina; Nurkholisah, Siti; Nugroho, Afrizal Eko (Al-'Adl, 2025)
This study aims to analyze and compare the changes to the adultery articles in the Criminal Code (KUHP) and the National Criminal Code (KUHP), and to examine the Islamic legal values ​​contained in these regulations. Internalization is expected to strengthen national morality, protect morality, and maintain public order. The Criminal Code only regulates adultery as sexual intercourse involving married parties, making it irrelevant to the moral values ​​of Indonesian society, which uphold religious and moral norms. Meanwhile, the National Criminal Code broadens the scope of adultery to include any sexual intercourse outside of marriage, whether the perpetrators are married or not. The urgency of this research lies in the importance of reforming national criminal law to better reflect the moral, social, and religious values ​​entrenched in Indonesian society. The old Criminal Code, a legacy of Dutch colonialism, is no longer relevant for its full implementation because it is built on liberal principles and values ​​that conflict with the character of the Indonesian nation, which is based on Pancasila. This research is a normative legal study using a statute approach and a conceptual approach, followed by descriptive and analytical analysis. The research findings indicate that the amendment to the adultery article in the National Criminal Code not only broadens the scope of the crime of adultery but also reflects the internalization of Islamic legal values ​​into the national criminal law system. Thus, the new Criminal Code represents a harmonization of positive law and religious moral values, consistent with the character of the Indonesian nation, which is based on Pancasila. This research not only classifies adultery perpetrators as married and unmarried but also examines how Islamic legal values ​​contributed to the formation of the National Criminal Code.